Peran Kepercayaan Merek Dalam Memediasi Pengaruh Kepuasan Pelanggan Terhadap Loyalitas Produk Telepon Pintar Merek Apple di Kota Denpasar - Putra, Bariocha Benaya Brendana; Sulistyawati, Eka (E-Jurnal Manajemen, 2014)
This study aims to analyze the influence of customer satisfaction on brand trust ,brand trust on brand loyalty, customer satisfaction on brand loyalt y, and the mediating role of brand trust on Apple smart phone products in Denpasar. This research is an associative study aimed to examine the relationship of each variable. Sampling technique is purposive sampling by adding certain criteria that are considered representative of the population . The results showed that : First , customer satisfaction has positive and significant effect on brand trust. Second, brand trust has positive and significant effect on brand loyalty Third, customer satisfaction has positive and significant effect on brand loyalty.Fourth, brand trust has signficant effect on mediates the effect of customer satisfaction on brand loyalty with a significant level variables . Based on the discussion and the conclusion it is suggested to the manager of Apple to continuously innovate in order to improve consumer satisfaction and loyalty. Keywords :Customer Satisfaction , Brand Trust , Brand Loyalty